2000
DOI: 10.1093/toxsci/53.1.127
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Effects of Nose-Only Inhalation Exposure on Testicular Toxicity in Male Rats

Abstract: Reductions in testicular mass, sperm motility, and mating frequency have been attributed to the stresses caused by confinement of Sprague-Dawley male rats in nose-only inhalation exposure tubes. Testicular changes, including an increase in testicular atrophy, have been detected at an increased incidence in male rats used in inhalation studies as compared with rats of the same age and strain used in oral toxicity studies. This study was designed to determine whether nose-only exposure of male rats caused testic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…7). Tubular degeneration and epididymal changes attributed to the injury caused by the confinement of rats in nose-only inhalation exposure tubes were consistent to procedure-related effects described in the literature (Rothenberg et al 2000). Therefore, subtle changes in testis weights could not be concluded as a nicotine effect reported previously for orally or subcutaneously administered nicotine (Aydos et al 2001;Oyeyipo et al 2010); however, the testicular degeneration is consistent with the phenomenon reported for restrained rats, even in controls for inhalation exposure (Lee et al 1993).…”
Section: Effects On Non-respiratory Organssupporting
confidence: 83%
“…7). Tubular degeneration and epididymal changes attributed to the injury caused by the confinement of rats in nose-only inhalation exposure tubes were consistent to procedure-related effects described in the literature (Rothenberg et al 2000). Therefore, subtle changes in testis weights could not be concluded as a nicotine effect reported previously for orally or subcutaneously administered nicotine (Aydos et al 2001;Oyeyipo et al 2010); however, the testicular degeneration is consistent with the phenomenon reported for restrained rats, even in controls for inhalation exposure (Lee et al 1993).…”
Section: Effects On Non-respiratory Organssupporting
confidence: 83%
“…These investigations demonstrated convincingly a retardation of body weight gain, even in air-exposed controls, as evidenced by a rise in body weight in the postexposure phase immediately following the termination of subchronic or chronic tube exposures ( Figure 6 ). Rothenberg et al (2000) found that even short daily nose-only tube exposures of rats to air for 42 d resulted in a 24% lower body weight, although no adverse effects on testes or reproductive performance was found. Pauluhn and Mohr (1999) confirmed this effect of nose-only exposure on body weight reduction in a 4-wk study in rats.…”
Section: Strategy/concepts Of Inhalation Testing For Cnt/cnf Toxicitymentioning
confidence: 89%
“…The former requires individual placement of rodents in compartmentalized areas in order to avoid huddling of the animals and permits some free movement, whereas their movement is severely restricted by placing them in narrow tubes during nose-only exposure with the noses protruding into the plenum with continuously supplied aerosol. This induces significant stress in the animals ( Phalen 2009 ), as evidenced by a retarded body weight gain during longer term nose-only exposures ( Coggins et al 1993 , 2011 ; Pauluhn and Mohr 1999 ; Rothenberg et al 2000 ). In contrast, contamination of the fur by aerosolized materials is restricted to the head and perhaps shoulder area, whereas during whole-body exposure aerosol deposition occurs on the whole-body surface area, resulting in some additional gastrointestinal (GI) tract exposure due to preening (see more discussion under “Types of Inhalation”).…”
Section: Dosing Methods For the Respiratory Tractmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased body weight gains were observed on day 2, but they did not show a doseresponse relationship and normal body weight gain was restored on day 7. The difference was presumed to be related to the additional stress of handling and placement of rats in the exposure tubes and the additional time spent away from the feed containers (Rothenberg et al, 2000) .…”
Section: Discussionmentioning
confidence: 99%